An annotated key to the Bovista (Lycoperdaceae, Basidiomycota) species in Russia - Rebriev, Yury A.; Ge, Zai-Wei; Voronina, Elena Y.; Fomina, Elena S.; Nazarenko, Alexander V. (Phytotaxa, 2020)
The present paper deals with Bovista species diversity in Russia. Morphological features of the genus are presented as well as geographical distribution in Russia and globally. We present a phylogenetic tree and the correlation of molecular data and morphology is discussed. An identification key for 16 species known in Russia from herbarium collections is provided as well as SEM and LM images of basidiospores and capillitium of these species. According to morphological and genetic data three taxa are probably undescribed. We need additional collections for these species in order to describe them as new. The variability of the polymorphic Bovista aestivalis and some other species is discussed too.